2018
DOI: 10.3319/tao.2018.03.11.01
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analyses on the ionospheric total electron content related to M ≥ 6.0 earthquakes in China during 1998 - 2015

Abstract: To verify the pre-earthquake ionospheric anomaly (PEIA), statistical analyses are implemented on the relationship between the total electron content (TEC) of global ionosphere map (GIM) and 62 M ≥ 6.0 earthquakes in China during 1998 -2015. A median-based method together with z test is employed to determine the criteria and/or characteristics of TEC anomalies related to earthquakes. , 18 -20 days before 7 M ≥ 7.0 earthquakes. The receiver operating characteristic (ROC) curve is used to compare the TEC anomaly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(73 citation statements)
references
References 21 publications
6
66
1
Order By: Relevance
“…September, its polarity (positively anomalous) agrees with statistical results of the pre-EQ TEC anomalies over Japan [Kon et al, 2011;Liu et al, 2013]. However, we are afraid that this is also a geomagnetic effect, because this kind of positive anomaly appears almost everywhere around the world, though the Dst index is about -20 nT, only a small disturbance.…”
Section: Upper Ionospheric Perturbation As Detected By Tec Datasupporting
confidence: 79%
“…September, its polarity (positively anomalous) agrees with statistical results of the pre-EQ TEC anomalies over Japan [Kon et al, 2011;Liu et al, 2013]. However, we are afraid that this is also a geomagnetic effect, because this kind of positive anomaly appears almost everywhere around the world, though the Dst index is about -20 nT, only a small disturbance.…”
Section: Upper Ionospheric Perturbation As Detected By Tec Datasupporting
confidence: 79%
“…Other ionospheric parameters usually change several days before earthquakes. For example, the statistical studies have reported that ion density perturbations occur 5 days before (Yan et al, 2017); total electron content significantly decrease 2–9 days before (Liu et al, 2013), and abnormal decrease of the ionospheric foF2 occurs within 5 days before the earthquakes (Liu et al, 2006). Our statistical results indicate that the time scale of pre‐earthquake ULF disturbances in the ionosphere is similar to other ionospheric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies suggest that anomalous ULF wave activity before earthquakes is recorded by satellites in the ionosphere, such as the Swarm and the DEMETER satellites (De Santis et al, 2017; Walker et al, 2013). On the other hand, it is now well established that other ionospheric parameters, for instance, electron/ion density, total electron content, and ELF/VLF wave intensity, have shown pre‐earthquake effects (e.g., Liu et al, 2013; Němec et al, 2008; Yan et al, 2017). However, previous studies have not dealt with the statistical relationship between ULF wave activity in the ionosphere and earthquakes.…”
Section: Introductionmentioning
confidence: 99%
“…The NT analysis could be applied to any discrete time series with fixed (or not fixed) time spacing. However, we did not need to perform the NT analysis with the 30 s data, because the pre-seismic processes related to the LAIC usually had a much longer time scale of a day to a few weeks (e.g., [ 3 , 5 , 9 ]).…”
Section: Datamentioning
confidence: 99%
“…The ionospheric perturbations mainly appear in two ways. One way is the variations in the F-region electron density and is further seen in the total electron content (TEC) (e.g., [ 3 , 4 , 5 , 6 ]). The other way is the fluctuations in the bottom ionosphere observed using very low-frequency (VLF) and low-frequency (LF) radio wave techniques.…”
Section: Introductionmentioning
confidence: 99%